1982
DOI: 10.1084/jem.155.4.1210
|View full text |Cite
|
Sign up to set email alerts
|

Clearance of circulating DNA-anti-DNA immune complexes in mice.

Abstract: Immune complexes composed of DNA and antibodies to DNA contribute to tissue injury in systemic lupus erythematosus (SLE) (1, 2). High titers of antibodies to both single-stranded DNA (ssDNA) and double-stranded DNA (dsDNA) are associated with the disease (2, 3), and antibodies to DNA have been eluted from the kidneys of SLE patients (4, 5). Direct demonstration of circulating DNA-anti-DNA immune complexes has been reported (6, 7), but not confirmed (8).Whereas the fate of circulating immun e complexes such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

1982
1982
2000
2000

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 15 publications
1
28
0
Order By: Relevance
“…DNA itself was cleared rapidly from the circulation by digestion with circulating nucleases and by hepatic binding (5,6,7). Immune complexes containing large DNA were cleared from circulation at the same rate and with the same distribution as DNA alone (8). Studies by Harbeck et al (9) suggested that DNase is able to digest DNA away from the DNA-anti-DNA complex, and can thereby release free antibody.…”
mentioning
confidence: 79%
“…DNA itself was cleared rapidly from the circulation by digestion with circulating nucleases and by hepatic binding (5,6,7). Immune complexes containing large DNA were cleared from circulation at the same rate and with the same distribution as DNA alone (8). Studies by Harbeck et al (9) suggested that DNase is able to digest DNA away from the DNA-anti-DNA complex, and can thereby release free antibody.…”
mentioning
confidence: 79%
“…However, it has not been possible to demonstrate routinely the presence of DNA, either free in the circulation or bound in immune complexes, in patients with SLE (37). DNA-anti-DNA complexes prepared ex vivo and injected into animals showed no affinity for glomerular basement membrane (GBM), and were rapidly cleared from the circulation by the reticuloendothelial system (38). In addition, it seems unlikely that the negatively charged DNA in the immune complex could bind easily to the negatively charged GBM.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue deposition of DNA-anti-DNA immune complexes has been regarded as a prerequisite in disease pathogenesis [3,4]. However, it remains doubtful whether this represents the predominant pathogenic mechanism, in view ofthe inconsistent detection of circulating immune complexes, and the failure to produce similar pathologies upon injection of pre-formed immune complexes in animal experiments [5,6]. Cross-reactivity of anti-DNA antibodies towards a heterogeneous group of cellular and extracellular components has been demonstrated Correspondence: Dr T. M. Chan, Department of Medicine, 4th floor.…”
Section: Introductionmentioning
confidence: 99%